1990
DOI: 10.1007/pl00020013
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of acute spinal cord injuries

Abstract: The injury was performed with 600g-cm/weight on the spinal cord of 40 cats with T8-9 laminectomy in this study. Ten cats were given 10 mg/kg naloxone i.v. 1 h after injury. Ten cats were given 2 mg/kg thyrotropin-releasing hormone (TRH) i.v. l h after injury followed by lmg/kg per hour for 4 h. Intravenous lidocaine was begun 30 rain after injury in ten cats, administered as 1.5mg/kg over the initial 5min, 3mg/kg over the next 30 min and 1 mg/kg every 30 min for 4 h. The remaining ten cats were given only sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…(C) A significant correlation was detected between lesion volume values obtained with the two methods (P < 0.05, regression ANOVA). a variety of experimental models of CNS trauma in a number of species (Akdemir et al, 1993;Arias MJ, 1987;Behrmann et al, 1994;Ceylan et al, 1990Ceylan et al, , 1992Faden, 1989Faden, , 1993Faden et al, 1981Faden et al, , 1990Fukuda et al, 1979;Puniak et al, 1991;Takami et al, 1991;Wang and Zhu, 1991). A small clinical study confirmed these beneficial effects in human spinal cord injury (Pitts et al, 1995).…”
Section: Figmentioning
confidence: 99%
“…(C) A significant correlation was detected between lesion volume values obtained with the two methods (P < 0.05, regression ANOVA). a variety of experimental models of CNS trauma in a number of species (Akdemir et al, 1993;Arias MJ, 1987;Behrmann et al, 1994;Ceylan et al, 1990Ceylan et al, , 1992Faden, 1989Faden, , 1993Faden et al, 1981Faden et al, , 1990Fukuda et al, 1979;Puniak et al, 1991;Takami et al, 1991;Wang and Zhu, 1991). A small clinical study confirmed these beneficial effects in human spinal cord injury (Pitts et al, 1995).…”
Section: Figmentioning
confidence: 99%
“…17,18 This work was successfully extended to brain injury models, and the neuroprotective actions of such compounds were confirmed by many laboratories. Indeed, in direct comparison studies, TRH or TRH analogues have been shown to be more effective than many of the other major proposed neuroprotective strategies, including highdose methylprednisolone, [19][20][21] opiate antagonists, [21][22][23][24] NMDA antagonists, 25 calcium channel blockers, 26 serotonin antagonists, 23 and neurotensin antagonists, among others. 21 In addition, a small clinical trial of TRH suggested protective effects after spinal cord injury in humans.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence in animals and in human beings that TRH and its analogs may decrease secondary injury after SCI and improve neurological recovery. 1,2,7 Proposed mechanisms of efficacy include antagonism of endogenous opioids, peptidoleukotrienes, platelet-activating factors, and excitotoxins. 8 In rodent models of SCI, TRH can improve functional locomotion and decrease the amount of secondary injury.…”
Section: Combination Of Medications Have Been Effective In Treating Mmentioning
confidence: 99%